POST-COVID INTOXICATION SYNDROME IN CHILDREN: CLINICAL, LABORATORY, AND FUNCTIONAL CHARACTERISTICS - Ahmadova Marzhona Rakhmatulloevna (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
Abstract: Post-COVID Intoxication Syndrome (PCIS) in children is an emerging clinical condition characterized by persistent metabolic, neurological, and autonomic dysfunction following recovery from SARS-CoV-2 infection. The syndrome is associated with chronic fatigue, decreased physical tolerance, impaired cognitive performance, and laboratory signs of ongoing inflammatory and metabolic overload. The purpose of this study was to evaluate clinical symptoms, laboratory parameters, and functional responses in children affected by PCIS, with particular focus on identifying diagnostic markers and risk factors that influence the severity of the syndrome.